Technical and economic analysis of the extraction of polyphenolic and fiber residues from Araucan cocoa husk of clone CCN51 (2024)
Cocoa pod husk is a waste product obtained after cocoa production which represents 75% w/w of the cocoa pod and is a reliable source of insoluble fiber and polyphenols. The present work studied the polyphenols and fiber extraction using dry and inactivated cocoa pod husk of clone CCN51 from Arauca, Colombia. To achieve this, a technical and economic analysis is made. For the technical analysis, four simulations were made considering the characterization of clone CCN51 husk, the Araucan production, and the viability and impact of solvent reflux and energy recovery. Then, each alternative's economic analysis was developed using economic projections and financial performance indicators. The technical results showed the efficiency of the polyphenols extraction in all scenarios was 73%, and a recovery of 61,26% of the cocoa pod husk. The economic results showed that with solvent reflux and energy recovery, the investment can be recovered in one year (payback), and the process's net present value (NPV) is $6.671.017.888. This demonstrates the huge opportunity that the extraction of these components represents for the region, making cocoa crops more profitable for those who have changed the illicit crops for this product.